If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 42y + 38 = 32 Reorder the terms: 38 + 42y = 32 Solving 38 + 42y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-38' to each side of the equation. 38 + -38 + 42y = 32 + -38 Combine like terms: 38 + -38 = 0 0 + 42y = 32 + -38 42y = 32 + -38 Combine like terms: 32 + -38 = -6 42y = -6 Divide each side by '42'. y = -0.1428571429 Simplifying y = -0.1428571429
| 49.5=9h | | 1x+12=18 | | -6+x/2=10 | | w+5sqrt(w)=-7sqrt(w)+(w+6) | | 0=-5x^2+13x-5 | | 6x^2+-18x-18=6 | | -3-8(n-1)=19+6n | | 5a^2+26a-24=0 | | xy-8x=8y | | x^4-x^2-x=x-255 | | 2x+9x=81 | | X^2*3x=0 | | p+(26)=-13.8 | | X+43+43=180 | | -3x-8=8+5x | | 2-3(2+6z)=4(z+1) | | x^4-x^2-x=x+255 | | 3x+4=8x+4+140 | | 8(-9)-6=5(-9) | | 12x-8x=12-6x | | 17-2x=-43 | | -2(4s-5)-10=-3(8s+3)-5 | | 6x^2-84x+294= | | 3n+15=n+25 | | 2-5(5x-5)=73 | | -3(x+1)=2x+12 | | x^2-10x-19=5 | | 4(6x+2)=-3(4x-3)-19 | | h(x)=14e^7x^5+2x | | -5x^2-29= | | 4(x+6)+3=4x+5 | | 6ln(3x+2)=10 |